The Role of Human Chorionic Gonadotropin Beta (hCGβ) in HPV-Positive and HPV-Negative Oropharyngeal Squamous Cell Carcinoma - Sjöblom Anni; Carpén Timo; Stenman Ulf-Håkan; Jouhi Lauri; Haglund Caj; Syrjänen Stina; Mattila Petri; Mäkitie Antti; Hagström Jaana (Switzerland, 2022)
Background: This study was carried out to observe the upregulation of the free β-subunit of human chorionic gonadotropin (hCGβ) and its prognostic significance in human papillomavirus (HPV)-positive and HPV-negative oropharyngeal squamous cell carcinoma (OPSCC).
Materials and methods: A total of 90 patients with OPSCC treated with curative intent at the Helsinki University Hospital (HUS), Helsinki, Finland, during 2012-2016 were included. Serum samples were collected prospectively, and their hCGβ concentrations (S-hCGβ) were determined by an immunofluorometric assay. The expression of hCGβ in tumor tissues was defined by immunohistochemistry (IHC). HPV determination was performed by combining p16-INK4 IHC and HPV DNA PCR genotyping. Overall survival (OS) and disease-specific survival (DSS) were used as survival endpoints.
Results: S-hCGβ positivity correlated with poor OS in the whole patient cohort (p < 0.001) and in patients with HPV-negative OPSCC (p < 0.001). A significant correlation was seen between S-hCGβ and poor DSS in the whole cohort (p < 0.001) and in patients with HPV-negative OPSCC (p = 0.007). In a multivariable analysis, S-hCGβ was associated with poor DSS. Of the clinical characteristics, higher cancer stage and grade were associated with S-hCGβ positivity. No statistically significant correlation with tissue positivity of hCGβ was seen in these analyses.
Conclusion: S-hCGβ may be a potential independent factor indicating poor prognosis, notably in HPV-negative OPSCC.